Seven Non-melanoma Features to Rule Out Facial Melanoma - Philipp Tschandl; Alessio Gambardella; Amélie Boespflug; Teresa Deinlein; Vincenzo de Giorgi; Harald Kittler; Aimilios Lallas; Josep Malvehy; Elvira Moscarella; Susana Puig; Massimiliano Scalvenzi; Luc Thomas; et al. (Medical Journals Sweden, 2017)
Facial melanoma is difficult to diagnose and dermatoscopic features are often subtle. Dermatoscopic non-melanoma patterns may have a comparable diagnostic value. In this pilot study, facial lesions were collected retrospectively, resulting in a case set of 339 melanomas and 308 non-melanomas. Lesions were evaluated for the prevalence (> 50% of lesional surface) of 7 dermatoscopic non-melanoma features: scales, white follicles, erythema/reticular vessels, reticular and/or curved lines/fingerprints, structureless brown colour, sharp demarcation, and classic criteria of seborrhoeic keratosis. Melanomas had a lower number of non-melanoma patterns (p < 0.001). Scoring a lesion suspicious when no prevalent non-melanoma pattern is found resulted in a sensitivity of 88.5% and a specificity of 66.9% for the diagnosis of melanoma. Specificity was higher for solar lentigo (78.8%) and seborrhoeic keratosis (74.3%) and lower for actinic keratosis (61.4%) and lichenoid keratosis (25.6%). Evaluation of prevalent non-melanoma patterns can provide slightly lower sensitivity and higher specificity in detecting facial melanoma compared with already known malignant features.